NONLINEAR SELF-TUNING REGULATOR FOR PH SYSTEMS - LEE, SD; LEE, JT; PARK, SW (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
A nonlinear self-tuning regulator for controlling the pH value of weak acid streams by a strong base is proposed. The nonlinear state equations describing the neutralization process are transformed so that we can estimate the unknown parameters, the concentration and the dissociation constant of the influent weak acid, via the recursive least squares method with a variable forgetting factor. Then we apply the one-step-ahead control law. Simulation results show that the regulator provides good performance for realistic situations such as multicomponent weak acid and strong base systems.